2018
DOI: 10.1242/jcs.208223
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and stromal circadian clocks are inversely regulated by their mechano-matrix environment

Abstract: The circadian clock is an autonomous molecular feedback loop inside almost every cell in the body. We have shown that the mammary epithelial circadian clock is regulated by the cellular microenvironment. Moreover, a stiff extracellular matrix dampens the oscillations of the epithelial molecular clock. Here, we extend this analysis to other tissues and cell types, and identify an inverse relationship between circadian clocks in epithelia and fibroblasts. Epithelial cells from mammary gland, lung and skin have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
(35 reference statements)
2
28
0
Order By: Relevance
“…In the U2OS osteosarcoma line, BMAL1 over-expression induces apoptosis, while in CA46 lymphoma cells it increases apoptosis and reduces proliferation, leading to smaller tumours when the cells are injected into mice [ 5 ]. Stromal cells are the origin of osteosarcoma cells, and we have examined clocks in stromal cells [ 52 ]. We found that stromal clocks are regulated oppositely to those in epithelial cells in normal tissues, so it will be interesting to determine possible alterations of clock gene expression in the normal and tumour-associated stromal regions of breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the U2OS osteosarcoma line, BMAL1 over-expression induces apoptosis, while in CA46 lymphoma cells it increases apoptosis and reduces proliferation, leading to smaller tumours when the cells are injected into mice [ 5 ]. Stromal cells are the origin of osteosarcoma cells, and we have examined clocks in stromal cells [ 52 ]. We found that stromal clocks are regulated oppositely to those in epithelial cells in normal tissues, so it will be interesting to determine possible alterations of clock gene expression in the normal and tumour-associated stromal regions of breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Still, adequate customizable models to study these complex interactions are still lacking. In vitro studies using traditional 2D models have provided important insights into relevant pathophysiological processes occurring in breast tissue, and associated mechanisms (Kozlowski et al, 2009;Sung et al, 2013;Jin et al, 2018;Williams et al, 2018). Still, 2D models are reductionist as they fail to recapitulate key architectural features of healthy and diseased tissues, namely by lacking three-dimensionality, forcing artificial cell polarity and failing to mimic native biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…; Williams et al . ). As such, disruption of any single ECM component can, and often does, lead to an enormous array of downstream changes that typically force the establishment of a new dynamic equilibrium and underpin the gross changes in tissue and organ architecture and function typically associated with cancer progression (Mayorca‐Guiliani et al .…”
Section: Defining the Ecm In Health And Diseasementioning
confidence: 97%